Recovering non-pecuniary losses in breach of employment contract under Malaysian law - Ali Mohamed, Ashgar Ali (OCERINT International Organization Center Of Academic Research, 2017)
This paper discusses the high-handed manner of a dismissal, its impact on the employee and the availability of compensation for non-pecuniary losses under the statutory unfair or unjustifiable dismissal. Reference is made to the law and practice in selected countries namely, the United Kingdom, Canada, Australia and New Zealand. In the context of Malaysia, it will be contended that an employee that had been subjected to deplorable acts of victimisation while in employment and any highhanded manner of a dismissal, among others, should be awarded the non-pecuniary compensation.